Design of 7-Level Hybrid Inverter Control Circuit - Thejel, Rabee Hashim (Iraqi Journal for Electrical and Electronic Engineering, 2006)
Use of multilevel inverters is becoming popular in the recent years for high power applications. The important feature of these inverters is of having low harmonics content in the output voltage. The switching angles in a multilevel inverter are computed so as to produce an ac output voltage with minimum harmonics. A new control circuit is designed to achieve these angles. This control circuit has the ability to control the RMS output voltage using sinusoidal pulse width modulation (SPWM). The results presented in this work prove the ability of the designed control circuit to gain the required ac output voltage with minimum distortion.